Adult Onset Still´s Disease (AOSD): A rare condition with a classic presentation. Case Report - Andrés Eduardo Prieto-Torres; Wilson Suárez-Molina; Jaime Iván Pantoja-Agreda (Case Reports)
Introduction: Adult Onset Still´s Disease (AOSD) is a rare systemic inflammatory disease of unclear etiology, with low incidence and prevalence among the general population. AOSD is a common cause of fever of unknown origin (FUO) in up to 20% of cases. Due to the scarce knowledge about this disease and its diagnosis, it is usually unrecognized in the differential diagnoses, worsening the prognosis and increasing complications in some patients.